VAN GÖLÜ ÇEVRESİNDE ŞAMANİZM İZLERİ - KAPLAN, İBRAHİM (Fırat Üniveristesi, 2010)
Milletlerin karakterini ortaya koyan; onların sürekliliğini sağlayan en önemli unsurlardan biri kültürdür. Kültürün sürekliliğini sağlayan ise inançlardır. Bu inançlar sadece mensubu olunan dinler değil; aksine milletlerin tarihleri boyunca inandıkları bütün inançlardır.Türk inanç tarihinde Türk kültürü üzerinde etkili olan en önemli inanç ise Şamanizm'dir. Bütün dünya Şamanizmlerinden farklı olan Türk Şamanlığı Türk gelenek, görenek ve yaşam tarzına sinmiştir. Van Gölü çevresinde görülen gelenek, görenek ve yaşam tarzında Türk Şamanlığı, Şamanizm'in kutsal unsurları yoluyla hâlâ yaşamaktadır.Çalışmamızın amacı; günümüz inançları ile eski inançların ortak noktalarını tespit etmekti. Çalışmamızın sonunda bulgularımız aradaki ilginin bir benzerlikten öte olduğunu göstermiştir. Türk Şamanlığı; günümüz inançları, gelenek ve görenekleri içerisinde bazen hiç değişmeden bazen de inanç parçacıkları şeklinde yaşamaktadır.Anahtar Kelimeler: Şamanizm, Türk Şamanlığı, kültür

Culture is one of the most important elements that helps to shape the character of a nation and maintain the continuity and existence of the nation. Whatever makes the continuity and existence of the nation is its beliefs. These beliefs inclade not only the current religious beliefs that the nation believes but also all other religions which the nation has had throughout its history for ages.In the history of Turkish beliefs, Shamanism has been the most important belief which has had a considerable effect in Turkish culture. Turkish Shamanism which is for more different from all other world Shamanism has penetratet Turkish culture, customs, traditions and life style. Turkish Shamanism in the customs, traditions and life style of people living around the Lake Van.The aim of our studies is to determine the common points of current beliefs and the beliefs of past. The findings which we have had in the end of our studies indicate that relationships between the current beliefs and the beliefs of past have in common are beyond the similarities. In conclusion we can say that Turkish Shamanism still exists in the customs, traditions and beliefs of today either partly being changed or remaining unchanged.Key Words: Shamanism, Turkish Shamanism, culture
The traces of Shamanism the lake Van
Keywords: Halk Bilimi (Folklor)